A Study of Classroom Interaction Viewed From Information Sources at SMK PGRI 2 Gianyar - Ni Kadek Citawati; Pande Agus Adiwijaya; Luh Made Dwi Wedayanthi (The Future of Education Journal, 2025)
This study aimed to analyze the implementation of classroom interaction categories in writing classes at SMK PGRI 2 Gianyar from the perspective of information sources and to identify the constraints in applying multi-way interaction. This qualitative descriptive research involved tenth-grade students and their English teacher as participants. Data were collected through classroom observations, interviews, and field notes, focusing on the interaction patterns during teaching and learning activities. The findings revealed that 20 categories of the FLINT System were applied during three observation sessions. From the perspective of information sources, the teaching and learning process tended to be dominated by two-way interaction, with the teacher acting as the primary source of information. Several constraints were identified in promoting multi-way interaction, including limited time allocation, lack of teaching variety, and students’ passive behavior during lessons. Interviews also highlighted issues such as students’ minimal responses, lack of initiative during discussions, and the perception that English is difficult to learn. These findings indicate the need for strategies to create more balanced and interactive classrooms, where students can actively participate and develop better communication skills. This study is expected to provide insights for teachers in designing more engaging and effective classroom interactions to support the implementation of the Merdeka Curriculum.